Recent advances in the interaction of ferroptosis and immune-mediated inflammation in cardiovascular disease: mechanisms and therapeutic potential - Wang, Zhihao; Dang, Yexing; Li, Yuanyuan; Zhang, Yu; Zhou, Shuye; Zhang, Zhiguo; Wang, Yuehui (Frontiers in Immunology, 2025)
Ferroptosis is an iron-dependent form of programmed cell death primarily characterized by the inactivation of glutathione peroxidase 4 (GPX4), accumulation of lipid peroxides (LPO), and disruption of intracellular antioxidant defenses. Recent studies have revealed a close interplay between ferroptosis and immune-mediated inflammation, both of which contribute significantly to the pathogenesis of cardiovascular diseases (CVDs). In innate immunity, ferroptotic cells release damage-associated molecular patterns (DAMPs), such as high-mobility group box 1 (HMGB1), which activate the TLR–NF-κB signaling pathway, promote macrophage polarization toward the pro-inflammatory M1 phenotype, and induce the activation of NOD-like receptor protein 3 (NLRP3) inflammasomes, thereby amplifying inflammatory responses. In adaptive immunity, Th17 cells exacerbate cardiomyocyte ferroptosis by upregulating long-chain acyl-CoA synthetase 4 (ACSL4) via IL-17A secretion, whereas regulatory T cells protect by stabilizing GPX4 through IL-10. This review systematically delineates the intricate network linking ferroptosis and immune-mediated inflammation in CVDs, emphasizing the mechanisms by which ferroptosis modulates immune cell function, inflammatory cytokine release, and the oxidative stress. Moreover, we examined the involvement of this interaction in the pathophysiology of various CVDs, including atherosclerosis, myocardial infarction, myocardial ischemia–reperfusion injury (MIRI), heart failure, and cardiac arrhythmia. In addition, we provide a detailed analysis of the clinical translational potential of emerging therapeutic strategies targeting the ferroptosis–immune-inflammation axis, including interventions such as iron chelators, antioxidants, inflammation modulators, small-molecule inhibitors, and herbal compounds. By integrating the latest findings from basic and clinical research, this review offers novel insights and a theoretical framework for precision therapy in CVDs.